The impact of velocity-based movement on electromyography activity in standard lower-limb strength exercises - Ferri-Caruana, A.; Muñoz-Gómez, E.; Mollà-Casanova, S.; Camarón-Mallén, P.; Serra-Añó, P. (Scientific Journal of Sport and Performance, 2023)
Previous research has shown that the velocity of movement can influence muscle activation. However, no studies have investigated the impact of movement velocity under the same load conditions on electromyography (EMG) activity in knee and hip extensors. This study aims to compare the mean muscle activation of gluteus maximus [GM], biceps femoris [BF], semitendinosus [ST] and rectus femoris [RF] in three hip extension exercises (i.e., squat [SQ], hip thrust [HT] and Bulgarian squat [BS]) with two different movement velocities (i.e., maximum velocity [MV] and controlled velocity [CV]). Fifteen physically active students participated. The mean EMG activity of all targeted muscles was measured. Maximum Voluntary Isometric Contraction was used to normalize EMG muscle activation. All muscles were activated to a greater extent in BS at MV than in the same exercise performed at CV. However, during the SQ exercise, EMG differences between velocities were only obtained for BF and GM, and in HT, only for GM (p < .05). In conclusion, higher velocity involves higher activation of the lower-limb muscles, depending on the physical test, and this can be used to better plan the functional recovery of injury, taking it into consideration for intensity progression and avoiding the risks of overly strenuous exercises.